Consideraciones acerca de la belleza en el Ordine de San Agustín de Hipona - Costarelli Brandi, Hugo Emilio (Universidad Nacional de Cuyo. Facultad de Filosofía y Letras. Instituto de Filosofía., 2005)

(untitled)
The following article brings an insight through one of the first works of Saint Augustin, but from a special view: beauty. Henee, it will be clear that beauty will become, in Augustin’s consideration as one of the main realities of his thought, an omnipresent property, a transcendental structure, which from its joyful perception man will need to prepare through the purifying path of liberal arts and philosophy. It will also be possible to appreciate that even when this author uses certain ancient-thoughtstructures on his reflections, it will be able, nevertheless, to State the birth of a proper and original view of the universe